Wholesale Payments and Financial Discipline, Efficiency, and Liquidity - Folkerts-Landau, D. (Washington, D.C. : International Monetary Fund, 1997)
Properly designed wholesale payments system can make a significant contribution to enhancing market discipline in the financial sector, reducing the risk of systemic disturbance and permitting a less extensive safety net for financial institutions. The objective of these reforms has been to achieve a reduction of the credit risk associated with the growth in intraday credit exposures that arises in net settlement systems and in real-time gross systems when the central bank provides daylight overdrafts. Intraday payments-related credit in net settlement systems has been reduced by restructuring payment systems into real-time gross settlement systems with collateralized overdrafts, while in the existing real-time gross settlement systems, the risk-abatement program currently in effect has taken the form of caps and charges on uncollateralized daylight credit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet